Surgical outcome of pars plana vitrectomy: a retrospective study in a peripheral tertiary eye care centre of Nepal - Subedi, S; Sharma, MK; Sharma, BR; Kansakar, I; Dhakwa, K; Adhikari, RK (Nepalese Journal of Ophthalmology, 2010)
Back ground: Trans-pars plana vitrectomy (TPPV) is an effective surgical procedure to retain the useful vision in vitreoretinal diseases. Objective: To evaluate the surgical outcome of pars plana vitreoretinal surgery. Study design: Retrospective non-comparative interventional case series. Materials and methods: A hospital-based retrospective interventional study of series of cases was carried out in retina clinic of Lumbini Eye Institute, Nepal, over a period of one-and-a-half years. Records of 64 patients who underwent vitreo-retina surgeries were reviewed. Demography, duration of symptoms, risk factors and indications, preoperative and post-operative visual acuity, intra-operative and post-operative complications were analyzed. Outcome measurement: The parameters studied were post-operative visual acuity and complications. Results: Of 64 patients, 61 % presented 2 months after the onset of symptoms. Preoperatively, 65.5 % had visual acuity of hand motions to 3/60 followed by perception of light only in 26.6 %.The main indication for TPPV was vitreous haemorrhage (VH), in 53 %. The visual acuity improved to better than 6/60 in patients with VH (68 %), whereas, overall, in 72 % of the subjects, it improved by 2 lines postoperatively. The commonest intra-operative complications were iatrogenic retinal break (5, 7.8%) at the sclerostomy site. Conclusion: The main indication for TPPV is vitreous haemorrhage. Useful vision can be restored by pars plana vitrectomy in the majority of the patients. Retinal break is the commonest complication of TPPV. Keywords: Trans-pars plana vitrectomy; vitreous haemorrhage; visual outcome; retinal break. DOI: 10.3126/nepjoph.v2i1.3703 Nep J Oph 2010;2(1) 39-44